Penyuluhan Tentang Teknik Menyusui Pada Ibu Menyusui - Windatania Mayasari; Asih Dwi Astutui; Sarah Rukhuwa (Jurnal Pengabmas Masyarakat Sehat (JPMS), 2020)
Breastfeeding is a government program that must be carried out by mothers after giving birth until the baby is 6 months or even 2 years old. However, it cannot be denied that the fact among the community shows that the breastfeeding process is actually not easy, many mothers fail in the breastfeeding process. The breastfeeding technique is a method of breastfeeding that is done by a mother to a baby, in order to meet the baby's nutritional needs. The breastfeeding technique is a way of giving breast milk to the baby by bringing the mother and baby's body position closer together correctly. Achieve successful breastfeeding requires knowledge of breastfeeding techniques.Keywords: breastfeeding technique, breastfeeding mothers.